2021
DOI: 10.1002/humu.24186
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of the reconstitution of PTEN function by translational readthrough ofPTENpathogenic premature termination codons

Abstract: The PTEN tumor suppressor gene is mutated with high incidence in tumors and in the germline of patients with cancer predisposition or with macrocephaly associated with autism. PTEN nonsense mutations generating premature termination codons (PTC) and producing nonfunctional truncated PTEN proteins are frequent in association with human disease. However, there are no studies addressing the restoration of full-length PTEN proteins from the PTC-mutated PTEN gene by translational readthrough. Here, we have performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Aminoglycoside antibiotics were shown to induce readthrough of all three PTEN nonsense mutants as assessed by expression of full-length PTEN protein in transfected CCOS-7 or U87 cells, with G418 as the most efficient readthrough inducer. Functional assays based on the assessment of Akt phosphorylation and nuclear localization confirmed that translational readthrough generated fully active PTEN protein ( 36 ). Studies in our lab confirmed the translational readthrough effect of G418 on these three frequent PTEN nonsense mutations, and also demonstrated a synergistic readthrough activity of G418 in combination with C47, a novel molecule identified in a chemical library screen ( 30 ).…”
Section: Readthrough Of Nonsense Mutations In Other Cancer-associated...mentioning
confidence: 86%
“…Aminoglycoside antibiotics were shown to induce readthrough of all three PTEN nonsense mutants as assessed by expression of full-length PTEN protein in transfected CCOS-7 or U87 cells, with G418 as the most efficient readthrough inducer. Functional assays based on the assessment of Akt phosphorylation and nuclear localization confirmed that translational readthrough generated fully active PTEN protein ( 36 ). Studies in our lab confirmed the translational readthrough effect of G418 on these three frequent PTEN nonsense mutations, and also demonstrated a synergistic readthrough activity of G418 in combination with C47, a novel molecule identified in a chemical library screen ( 30 ).…”
Section: Readthrough Of Nonsense Mutations In Other Cancer-associated...mentioning
confidence: 86%
“…Pharmacological induction of translational readthrough is aimed at restoring expression of full-length proteins from genes that carry nonsense mutations. This approach has been proven to work for several cancer-relevant genes, such as TP53 [ 9 ], APC [ 22 ] and PTEN [ 12 ]. However, the clinical use of aminoglycosides is limited as they cause nephrotoxicity [ 14 ] and ototoxicity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycosides such as G418 and Gentamicin have been shown to induce readthrough of nonsense mutations in cancer-relevant genes, e.g. TP53 [ 9 , 10 ], BRCA1 [ 11 ], and PTEN [ 12 ]. However, the clinical utility of aminoglycosides such as G418 is limited by their reported ototoxicity [ 13 ] and nephrotoxicity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN protein truncations generated by nonsense mutations are unstable proteins with impaired function, although those generated by nonsense mutations targeting the PTEN C-terminal tail retain most of their stability and PIP3 phosphatase activity in cells [ 12 , 13 ]. The BA226 epitope contains Arg233, which is one of the PTEN residues frequently targeted by nonsense mutations in human tumors and in the germline of PHTS patients, and it constitutes a suitable mAb to study PTEN C-terminal truncations downstream PTEN residue 239.…”
Section: Discussionmentioning
confidence: 99%